PEMANFAATAN KECERDASAN BUATAN MENCIPTAKAN PRODUK GANTUNGAN KUNCI SALAD BOZ - Cokki; Olivia Putri, Angely; Tiffany, Fransisca; Wijaya, Santrista; Natalya, Yenny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
This community service aims to enhance brand awareness for our partner, Salad Boz, a healthy culinary business. Team observations reveal that Salad Boz's promotional media lacks appeal and tends to be monotonous, failing to captivate consumer attention. To address this, the PKM team collaborated with the business owner to create engaging promotional media, specifically keychains with the Salad Boz logo created using artificial intelligence. The creative process includes conceptual planning, image creation, editing, and implementation. Although the design of the keychains involves artificial intelligence, human assistance remains essential. The PKM team also advises the partner to actively monitor current developments and explore other appealing promotional strategies for future marketing endeavors.